Evaluation of Regional Emission Control Based in Photochemical Air Quality Modelling - Rodríguez, Ángel; Saavedra, 1Santiago; Dios, María; Torres, Carmen; Souto, José A.; Casares, Juan; Soto, Belén; Bermúdez, José L. (IntechOpen, 2011)
None